1991
DOI: 10.1002/jhet.5570280505
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazoles. 6. Synthesis of novel heteroaryl 4‐pyrazolyl ketones

Abstract: The preparation of a variety of novel heteroaromatic analogues of benzophenone 2–11 characterized by a 4‐pyrazolyl moiety and a thienyl‐, azinyl‐ or diazinyl‐system starting from 1,4‐dilithiopyrazole is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…One route was inspired from previous work on heteroaryl 4-pyrazolyl ketones. 47 It consisted of using direct lithiation of the 4-bromo pyrazole (commercially available or synthesized in one step by monobromination of pyrazole) with 3 equivalents of n-BuLi, which gave the intermediate 1,4-dilithiopyrazole, which could in turn be converted into the formylated compound by adding dry dimethylformamide to the reaction mixture. In the course of optimizing the reaction, we found that some parameters were particularly crucial to enhance the yield.…”
Section: Synthesis Of the Organic Radicalmentioning
confidence: 99%
“…One route was inspired from previous work on heteroaryl 4-pyrazolyl ketones. 47 It consisted of using direct lithiation of the 4-bromo pyrazole (commercially available or synthesized in one step by monobromination of pyrazole) with 3 equivalents of n-BuLi, which gave the intermediate 1,4-dilithiopyrazole, which could in turn be converted into the formylated compound by adding dry dimethylformamide to the reaction mixture. In the course of optimizing the reaction, we found that some parameters were particularly crucial to enhance the yield.…”
Section: Synthesis Of the Organic Radicalmentioning
confidence: 99%
“…However, there are only few examples of pyrazole C-4 lithiation. [42][43][44][45] Such reactions proceed with low selectivity, due to competing deprotonation at C-5 [42] or isomerization of the 4-lithiopyrazole to the corresponding 5-lithiopyrazole. [46] This problem can be circumvented through the introduction of a second protecting group at C-5, [47] but the overall multi-step synthesis makes such an option not very attractive, in our opinion.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to 4-substituted pyrazoles would be reaction of 4-lithiopyrazoles with electrophiles. However, there are only a few examples of pyrazole C-4 lithiation, all based on bromine−lithium exchange. This reaction sometimes proceeds with low chemoselectivity due to competing deprotonation at C-5 , or isomerization of initially formed 4-lithiopyrazole to 5-lithiopyrazole .…”
Section: Introductionmentioning
confidence: 99%